Perancangan Desain UI/UX Aplikasi Penjualan Kaki Lima - Tombeng, Marchel; Mambu, Joe Yuan (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
In today's rapidly evolving digital landscape, mobile applications have become integral to everyday life, transforming interactions across various services, including food procurement. Despite the growing popularity of online food sales, challenges persist in ensuring accessibility and user satisfaction, particularly with traditional dishes like